Surgical Implications for Diagnosis and Treatment of Intestinal Aspergillosis in Pediatric Patients with ALL - Fischer, Janina; Simon, Thorsten; Hamprecht, Axel; Hos, Nina; Möricke, Anja; Cernaianu, Grigore; Tharun, Lars; Gruhn, Bernd; Plum, Georg; Dübbers, Martin (European Journal of Pediatric Surgery, 2018)
Background The incidence of invasive aspergillosis (IA) in children with hematooncological malignancies is increasing as a result of intensive treatment, immunosuppression, and extended use of broad-spectrum antibiotics. Infection of the GI tract by Aspergillus spp. is a rare and fatal complication, which often requires surgical diagnostic and therapeutic exploration.Objective The aim of this study was to determine the characteristics of symptomatic intestinal aspergillosis, diagnosis, treatment, and outcome of pediatric patients with an underlying hemato-oncologic disease.Patients and Methods We analyzed 2,307 German patients with acute lymphoblastic leukemia (ALL) from age 1 to 17 years registered in the AIEOP-BFM ALL 2000 study from 2000 to 2006. All reported adverse events were assessed for symptoms of IA and retrospectively reviewed for any sign or proof of intestinal involvement of IA.Results In this cohort, IA was reported in 30 of 2,307 patients while intestinal involvement was documented in five patients. Four of these patients had intestinal symptoms and three patients underwent explorative laparotomy. Among clinical cases with IA, gastrointestinal manifestation of IA mostly occurred in adolescent patients (10–16 years). Symptoms varied from abdominal tenderness and pain to constipation. Intestinal aspergillosis was proven by microbiological and histopathological examination and fungal infection was observed macroscopically in the jejunal lumen during surgery. Despite the extended surgery and antifungal therapy, outcome of disseminated IA with intestinal involvement remains poor.Conclusion Surgeons should be aware of surgical complications of intestinal aspergillosis in children with hematooncological diseases requiring exploration and resection. IA is a rare event and still difficult to diagnose due to unspecific abdominal symptoms. Thus, biopsy sampling is of utmost importance to ensure diagnosis, and resection of necrotic or perforated tissue should be attempted early.
Keywords: intestinal aspergillosis; pediatric; intestinal; ulcerations